Study the View of Customer with Reference to Online Shopping - Kanojia, Babita A. (SFIMAR Research Review, 2016)
We are living in an information technology age. Major businesses are going online. It is one of the ways in creating a more convenient, faster, and an increased revenue business. Online shopping is a form of electronic commerce which allows to customers to buy goods and services directly from a seller over the internet using a web browser. Online shopping reduces the physical buying of products or services. This process is called as business to consumer (B2C). It is also deals with B2B shopping. It enables the customer to browse the firm’s range of products and services, view photos or images of the products, along with information about the product specification, features and prices. The researcher has selected this study to view the importance of online shopping for customers. For that the researcher has framed certain objectives and hypotheses. The study is based on primary as well as secondary data.